2002
DOI: 10.1073/pnas.092016999
|View full text |Cite
|
Sign up to set email alerts
|

Siderophore-mediated signaling regulates virulence factor production in Pseudomonas aeruginosa

Abstract: Numerous bacteria secrete low molecular weight compounds termed siderophores that have a high affinity for iron ions. Siderophores have a well-documented role as iron-scavenging chemicals, chelating iron ions in the environment whereupon the ferrisiderophores reenter the bacterial cells by means of specific cell-surface receptors. The iron is then released for incorporation into bacterial proteins. Here we show that in addition to its role as an iron-scavenger, the siderophore pyoverdine that is secreted by Ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
525
2
8

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 527 publications
(552 citation statements)
references
References 47 publications
17
525
2
8
Order By: Relevance
“…This observation can be explained in terms of the self-regulatory nature of pyoverdine. In the case of the mutant, unlike in the wild-type, exogenous pyoverdine addition cannot induce autochthonous siderophore secretion because the mutant does not have the cellular machinery for siderophore synthesis (Lamont et al, 2002;Visca et al, 2007). Thus, its iron uptake would be limited to the extent permitted by the pyoverdine supplied externally.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation can be explained in terms of the self-regulatory nature of pyoverdine. In the case of the mutant, unlike in the wild-type, exogenous pyoverdine addition cannot induce autochthonous siderophore secretion because the mutant does not have the cellular machinery for siderophore synthesis (Lamont et al, 2002;Visca et al, 2007). Thus, its iron uptake would be limited to the extent permitted by the pyoverdine supplied externally.…”
Section: Resultsmentioning
confidence: 99%
“…Most of the enzymes involved in the ring-opening pathway are iron-dependent oxygenases that require a plentiful iron supply for optimum functioning (Dinkla & Janssen, 2003;Dinkla et al, 2001;Gibson & Parales, 2000). Considering the fact that only a small amount of free iron is available under physiological conditions, owing to its minuscule solubility at physiological pH, one can expect iron to be a limiting factor for microbial growth and proliferation (Lamont et al, 2002). This leads to a paradoxical situation, which has been reported in rhizospheric environments, where iron deficiency has been shown to induce aromatic secretion by plants, but utilization of those aromatics by rhizospheric micro-organisms including P. putida requires iron (Jin et al, 2007(Jin et al, , 2008(Jin et al, , 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Iron-regulated virulence factors of P. aeruginosa are overexpressed in mixed biofilms Lamont et al (2002) demonstrated that in addition to its role as an iron scavenger, the siderophore pyoverdine acts as a signaling molecule to control the production of at least three virulence factors (exotoxin A, an endoprotease and pyoverdine itself) that are major contributors to the ability of P. aeruginosa to cause disease. As pyoverdine production was increased in the mixed biofilms (Figure 4a), we hypothesized that the bacterium shows increased virulence when competing for iron with the fungus.…”
Section: Interspecies Competition Triggers Virulencementioning
confidence: 99%
“…the production of exotoxins and endoproteases [51], and biofilms [52]). Further research is needed to elucidate the complex interrelationships between putative social and other life-history traits.…”
Section: Discussionmentioning
confidence: 99%